Returning To Normalcy: Operational Radiology Recovery In Academic Radiology Departments Following The Covid-19 Pandemic (Journal of Pharmaceutical Negative Results, 2020)
With an emphasis on various recovery domains, including managing appointment availability, patient safety and workflow changes, and operational data and analytics, this article provides a current snapshot of how radiology departments nationwide are planning recovery from the baseline of the coronavirus disease 2019 pandemic. 114 academic radiology departments received an email survey via the Society of Chairs of Academic Radiology Departments list server. Three main areas are described using best practices and shared experiences based on data provided by the 38 survey participants:(1) recovery planning, (2) establishing a new normal, and (3) forecasting and measuring. The common strategies and preparations academic radiology departments have made to reopen imaging in the post-coronavirus disease 2019 world should be known by radiology practices. All of this should be carried out while preserving a secure and patient-focused setting and getting ready to lessen the effects of any upcoming pandemics or outbreaks.